Authenticity and Tourist Motivation Across Cultural Tourism Experiences: Keaslian dan Motivasi Wisatawan di Seluruh Pengalaman Wisata Budaya - Taniyev Ahmadjon (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Authenticity is crucial in modern tourism, where travelers seek meaningful cultural experiences beyond sightseeing. Specific Background: Authenticity in tourism is categorized into objective, constructive, and existential dimensions, yet their impact on tourist motivations remains underexplored. Knowledge Gap: Existing studies focus on authenticity’s link to satisfaction but overlook demographic influences and its role in different tourism types. Aims: This study examines how authenticity shapes tourist motivations, expectations, and satisfaction through qualitative methods, including interviews and case studies. Results: Tourists value different forms of authenticity—objective for tangible heritage, constructive for personal expectations, and existential for transformative experiences—affecting satisfaction and loyalty. Novelty: This study offers a multidimensional view of authenticity, showing its subjective and dynamic nature influenced by demographics and psychology. Implications: Tourism providers should create culturally sensitive, community-focused experiences to enhance satisfaction, sustainability, and destination appeal. Highlights: Tourist Preferences Differ – Objective, constructive, and existential authenticity appeal to different traveler motivations. Authenticity Shapes Satisfaction – Aligning tourism experiences with authenticity preferences fosters deeper engagement and loyalty. Cultural Sensitivity Matters – Community-centered, respectful tourism preserves heritage while meeting diverse tourist expectations. Keywords: Authenticity, Cultural Tourism, Tourist Motivation, Experiential Tourism, Destination Loyalty, Sustainable Tourism